ESTIMASI KANDUNGAN KARBON ORGANIK PADA SUBSTRAT MANGROVE TAMAN NASIONAL BALURAN - , MUHAMMAD FURQON, Dr. Erny Poedjirahajoe ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One of the ecological function of mangrove ecosystem is as important organic carbon storage in the tropics. The organic carbon stored in trees and mangrove substrate. This study aims to determine variations in organic carbon content of Baluran National Park along the physical and chemical factors of beach that influence it. Based on the organic carbon content can be estimated the organic carbon stored in mangrove substrate. This research was conducted at 4 Resort with transect method at (10x10)m 2 plot. From 26 mangrove locations, 170 samples was taken on the top and bottom substrate. Data were analyzed by : determination of substrate texture (hydrometer method)